The influence of succinate-containing drugs on physical performance and recovery after exercise - S. V. Radko; A. D. Dulepov (Фармакокинетика и Фармакодинамика)
An assessment of the influence of 2-ethyl-6-methyl-3-hydroxypyridine succinate (Mexidol) on the physical performance of small laboratory animals and recovery after exercise was made. As a result, it was found that a single application of Mexidol increases the endurance of animals, estimated as maximum swimming time, 1.57 times. With the course of the drug, there was a tendency to improve performance with access to the plateau after the 3rd week, similar to the comparative drug - bis {2 - [(2E) -4-hydroxy-4-oxobut-2-enyloxy] -N, N-diethylethanaminium} butanedioate.